PENGELOMPOKKAN TINGKAT PENYAKIT PADA SETIAP DAERAH DI JAWA TIMUR MENGGUNAKAN K-MEANS - Danang Abimanyu Iqbal Mahendra (LPPM Universitas Bina Bangsa, 2024)
Tuberculosis, also known as TB, is an infectious disease caused by the bacteria Mycobacterium tuberculosis. The main symptoms of pulmonary tuberculosis include a persistent cough lasting for more than three weeks, sometimes accompanied by bloody sputum, fever, night sweats, fatigue, and weight loss. According to data from the Indonesian Ministry of Health, in 2020, there were approximately 372,851 newly diagnosed cases of TB in Indonesia. The objective of this study is to determine the prevalence of the disease in each region. In this study, clustering was performed on each variable, namely TB, pneumonia, leprosy, and malaria. The clustering resulted in three cluster categories. Cluster 1 consists of the following areas: Malang, Jember, Sidoarjo, Bojonegoro, Gresik, and Surabaya (city). Cluster 2 represents provinces with a medium number of cases and includes Lumajang, Banyuwangi, Situbondo, Probolinggo, Jombang, Pasuruan, Tuban, and Lamongan. Cluster 3 consists of Pacitan, Ponorogo, Trenggalek, Tulungagung, Blitar, Kediri, Bondowoso, Mojokerto, Nganjuk, Madiun, Magetan, Ngawi, Kediri (city), Blitar (city), Malang (city), Probolinggo (city), Pasuruan (city), Mojokerto (city), Madiun (city), and Batu (city)